Effectivity of Gel Derived from Degumming Silkworm Cocoon Waste for Skin Pigmentation - Tanjung, Masitta; Jannah, Raudhatul (Pakistan journal of biological sciences, 2023)
Background and Objective: The trash produced by boiling silkworm cocoons during the degumming process still retains useful amino acids, such as sericin and fibroin, that can repair skin damage caused by exposure to ultraviolet light. This study seeks to examine the impact of utilising degumming silkworm cocoons (DSC) gel, derived from boiling waste, on the healing process of rat skin that has been subjected to Ultraviolet (UV) light, as well as the determination of the Sun Protection Factor (SPF) value. Materials and Methods: The research used a Completely Randomized Design (CRD) consisting of 5 treatment groups, namely the positive control, avobenzone, the group without avobenzone and DSC gel and the administration of DSC gel at 20, 40 and 60% for 14 days. The research used 25 male rats ( Rattus norvegicus ). Skin tissue was prepared for microscopical examination using the paraffin method combined with Hematoxylin and Eosin (H&E) staining. The data were analyzed statistically with the one-way ANOVA test and continued with the post hoc Duncan's test. Non-parametric data were carried out by the Kruskal Wallis test and continued with the Mann Whitney test. Results: The degumming silkworm cocoons (DSC) gel had a fairly high SPF value with an extra protection category of 7.10 at a concentration of 60%. The DSC gel had the potential to accelerate the recovery of skin as observed by the test subjects showing no wrinkles and redness. An increase in epithelial thickness and a decrease in melanocyte cells were also obtained from the treatment. Increasing the concentration of DSC gel also improved the skin recovery exposed to ultraviolet light. Conclusion: The effective and efficient concentration of cocoon degumming waste gel is 40-60%. The ability of silkworm cocoon degumming waste to rejuvenate UV-exposed skin suggests its future application as a topical preparation for promoting skin health.